2015
DOI: 10.1007/s00264-015-2895-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical result of plate osteosynthesis using a locking plate system through an anterior humeral approach for distal shaft fracture of the humerus that occurred during a throwing motion

Abstract: The results of the current study indicates that plate osteosynthesis using a locking plate system combined with interfragmentary lag screws through anterior humeral approach may be a favorable option for the surgical treatment of humeral shaft fractures in throwers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…In terms of rates of implant removal for pain relief, there was no significant difference between the anterolateral approach group (10.0%) and the posterior approach group (12.3%). Kim et al [45] reported a similar rate of implant removal (16.1%) following surgery using the anterolateral approach to that reported in the current study. However, in current study, implant removal was difficult in the posterior approach group due to scar tissue formation around the radial nerve.…”
Section: Bsupporting
confidence: 86%
“…In terms of rates of implant removal for pain relief, there was no significant difference between the anterolateral approach group (10.0%) and the posterior approach group (12.3%). Kim et al [45] reported a similar rate of implant removal (16.1%) following surgery using the anterolateral approach to that reported in the current study. However, in current study, implant removal was difficult in the posterior approach group due to scar tissue formation around the radial nerve.…”
Section: Bsupporting
confidence: 86%
“…Injury radiographs were reviewed, and the AO/Orthopaedic Trauma Association classification was used to classify the types of fractures. 8 Using simple radiography performed during the follow-up period (6,12,24, and 52 weeks after surgery), "union" was defined as the absence of a fracture line or the presence of a bridging callus. Shoulder and elbow joint ranges of motion (ROM) were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…3 Radial nerve dissection may be necessary in all surgical approaches to humerus due to close neighborhood of humerus and radial nerve. [20][21][22][23][24] Therefore, transient of permanent radial nerve injury may be seen. 25,26 We choose anterior approach in humerus shaft and distal diaphysis fractures, since it was possible to perform fixation without exposing the radial nerve.…”
Section: Discussionmentioning
confidence: 99%